Migration Ecology of North Atlantic Humpback Whales: Mapping Movements throughout the Annual Cycle - Kettemer, Lisa Elena (UiT The Arctic University of Norway, 2023)
Animal migration is a fascinating natural phenomenon where large numbers of animals embark on long-distance journeys, seeking out favorable environmental conditions and prey throughout the annual cycle. In this thesis, a range of techniques was used to fill major knowledge gaps in humpback whale ( Megaptera novaeangliae ) movement patterns and migration ecology in the North Atlantic Ocean. Satellite telemetry offered insights into the movements of a mother-calf pair throughout the entire migration, demonstrated connectivity between the Barents Sea, Norway, and Iceland within the same season, and allowed us to estimate the energetic cost of one of the longest-documented mammalian migrations. We show that whales can adapt their migration speed to compensate for time spent foraging during winter while successfully providing for a calf. Photo-id and hormone screening was used to describe the seasonality, spatial development, and demographic composition of a foraging site in the northern Norwegian fjords during winter. A female-biased sex ratio and high return rates demonstrate that this site has become an important part of the annual cycle predominantly for female humpback whales in the Northeast Atlantic. Finally, we provided the first estimates of pregnancy rates for Northeast Atlantic humpback whales. This thesis presented movement patterns inferred from a basin-wide satellite telemetry dataset collected over the last two decades. We identified distinct migration strategies, highlighting the variability of migration strategies within foraging sites and the limited influence of migration distance on migration strategy. Notably, some animals from the Northeast Atlantic spent no time in the breeding area before returning on their northward migration. In conjunction, the results presented in this thesis can inform ecosystem management and assessment of the species conservation status. The presented movement patterns are a valuable reference for future changes caused by continued climate change and increasing ...